Jackie Robinson papers - Robinson, Jackie, 1919-1972.
Correspondence, memoranda, telegrams, fan mail, speeches, writings, congressional testimony, baseball contracts, subject files, financial and legal records, military records, printed matter, and other papers relating chiefly to Robinson's career as a baseball player and corporate executive, and to his participation in political activities, religious and civic organizations, the civil rights movement, and media affairs. When Jackie Robinson began his career with the Brooklyn Dodgers in 1947, he broke the unwritten racial color line that had existed in major league baseball since the late nineteenth century, and a significant portion of the collection is devoted to his pioneering efforts in this regard. Topics also include the Albany movement, African independence movement, and economic development in the African-American community. Correspondents include Buzzie Bavasi, Roy Campanella, Happy Chandler, Charles Dressen, Alfred Duckett, Arthur Mann, Ralph Norton, Walter F. O'Malley, Joseph L. Reichler, and Branch Rickey.
Individuals represented include Chester Bowles, Barry M. Goldwater, W. Averell Harriman, Hubert H. Humphrey, Lyndon B. Johnson, Kenneth B. Keating, Robert F. Kennedy, Adam Clayton Powell, Nelson A. Rockefeller, Carl Thomas Rowan, and Malcolm X. Organizations represented include the African American Students Foundation, American Committee on Africa, Chock Full O'Nuts, Freedom National Bank, New York, N.Y., Jackie Robinson Foundation, National Association for the Advancement of Colored People, National Baseball Hall of Fame and Museum, New York Giants, Southern Christian Leadership Conference, and the U.S. Congress House Committee on Un-American Activities.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Baseball player, civil rights leader, and corporate executive. Full name: Jack Roosevelt Robinson.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bavasi, Buzzie -- Correspondence; Bowles, Chester, -- 1901-1986.; Campanella, Roy, -- 1921-1993 -- Correspondence; Chandler, Happy, -- 1898- -- Correspondence; Dressen, Charles -- Correspondence; Duckett, Alfred -- Correspondence; Goldwater, Barry M. -- 1909-1998.; Harriman, W. Averell -- 1891-1986.; Humphrey, Hubert H. -- 1911-1978.; Johnson, Lyndon B. -- 1908-1973.; Keating, Kenneth B. -- 1900-1975.; Kennedy, Robert F., -- 1925-1968.; Mann, Arthur -- 1901- -- Correspondence; Norton, Ralph -- Correspondence; O'Malley, Walter F. -- 1903-1979 -- Correspondence; Powell, Adam Clayton, -- 1908-1972.; Reichler, Joseph L., -- 1915- -- Correspondence; Rickey, Branch, -- 1881-1965 -- Correspondence; Rockefeller, Nelson A. -- 1908-1979.; Rowan, Carl T. -- 1925-2000.; X, Malcolm, -- 1925-1965.; United States. -- Congress. -- House. -- Committee on Un-American Activities; African American Students Foundation; American Committee on Africa; Brooklyn Dodgers (Baseball team); Chock Full O'Nuts.; Freedom National Bank (New York, N.Y.); Jackie Robinson Foundation; National Association for the Advancement of Colored People; National Baseball Hall of Fame and Museum; New York Giants (Baseball team); Southern Christian Leadership Conference; African Americans; African Americans -- Economic conditions; Baseball; Business; Civil rights movements; Mass media; Race discrimination; Africa -- Politics and government -- 20th century; United States -- Politics and government -- 20th century; United States -- Social life and customs -- 20th century; Baseball players; Civil rights leaders; Executives